2020
DOI: 10.1111/jasp.12709
|View full text |Cite
|
Sign up to set email alerts
|

Supporting immigrant cultural rights: The roles of deprovincialization and identity continuity

Abstract: This research examines the role of deprovincialization, conceptualized in terms of a nuanced perspective on one's in-group culture, for majority members' support for immigrants' cultural practices and expressive rights. In three studies using data from samples drawn from nationally representative panels in the Netherlands (additionally analyzed in an internal meta-analysis of N = 1,791), it was found that deprovincialization is a unique and robust predictor of support for immigrant rights, above and beyond pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In various Dutch national surveys, deprovincialization is indeed associated with the endorsement of multiculturalism and interculturalism (e.g., Verkuyten et al., 2020; Verkuyten, et al., 2010) and a relatively strong predictor of support for immigrant rights even after multiple controls (e.g., Verkuyten, Martinovic, & Smeekes, 2014). A small meta‐analysis establishes these robust associations with immigrant rights (Velthuis, et al., 2020; Verkuyten et al., 2016).…”
Section: Deprovincialization As In‐group Cultural Nuancementioning
confidence: 90%
See 1 more Smart Citation
“…In various Dutch national surveys, deprovincialization is indeed associated with the endorsement of multiculturalism and interculturalism (e.g., Verkuyten et al., 2020; Verkuyten, et al., 2010) and a relatively strong predictor of support for immigrant rights even after multiple controls (e.g., Verkuyten, Martinovic, & Smeekes, 2014). A small meta‐analysis establishes these robust associations with immigrant rights (Velthuis, et al., 2020; Verkuyten et al., 2016).…”
Section: Deprovincialization As In‐group Cultural Nuancementioning
confidence: 90%
“…It becomes more difficult to support minority cultural rights when the in‐group's cultural continuity is thought to be at stake. In two Dutch studies, it was found that in‐group continuity concern weakens, but does not reverse, the positive association between deprovincialization and support for minority cultural rights (Velthuis et al., 2020). The deprovincialized do defend to a greater degree the rights of immigrants more than other respondents even when they are concerned about the continuity of the cultural identity of their in‐group.…”
Section: Deprovincialization As In‐group Cultural Nuancementioning
confidence: 99%
“…The predisposition to be open-minded, empathetic, and generally well disposed toward others is considered to reflect a cognitive style and motivational orientation, and to be embedded in a person’s value orientations. Research reveals that the acceptance of a broad range of social groups is associated with lower need for closure (Roets & Van Hiel, 2011), higher cognitive ability (Dhont & Hodson, 2014), stronger perspective taking (Todd & Galinsky, 2014), a less parochial view on one’s own culture (Velthuis et al, 2020), and an endorsement of values such as universalism, benevolence, and egalitarianism (Davidov & Meuleman, 2012). Analyses of large-scale U.S. data from 1972 to 2006 show that the acceptance of a range of different practices from various groups is highly correlated (Chong & Levy, 2018; Davis, 2008).…”
Section: Modern Tolerance: the Prejudice–tolerance Continuummentioning
confidence: 99%
“…Cultural continuity concern was measured with three items (7-point scales), all starting with the introductory sentence 'immigrants in the Netherlands can live as they wish' (Velthuis et al, 2020). This was followed by three items that emphasized the importance of national cultural identity: '…as long as Dutch culture is preserved', 'if Dutch traditions continue to exist' and 'as long as Dutch identity is not undermined'.…”
Section: Design and Measuresmentioning
confidence: 99%
“…A sense of continuity has been conceptualized as an important identity need (Vignoles, 2011), and people will more strongly strive for cultural identity continuity when they perceive that it is challenged or threatened (see Smeekes & Verkuyten, 2015). Research has demonstrated that concern for cultural continuity can have negative implications for outgroup attitudes (e.g., Jetten & Wohl, 2012; Smeekes & Verkuyten, 2015) and for the acceptance of Muslim minority practices (Velthuis, Verkuyten, & Smeekes, 2020). In contrast, majority members who are little concerned about the continuation of their normative way of life tend to support cultural diversity and societal change, with the related recognition and acceptance of minority identities in various domains of life (Verkuyten, Yogeeswaran, Mepham, & Sprong, 2020).…”
Section: Cultural Continuity Concernmentioning
confidence: 99%